1993
DOI: 10.1111/j.1651-2227.1993.tb12717.x
|View full text |Cite
|
Sign up to set email alerts
|

The association between preterm newborn hypotension and hypoxemia and outcome during the first year

Abstract: Ninety-eight newborn infants, less than 34 weeks at birth, were studied to examine the relationship between newborn hypotension and hypoxemia and brain damage. Heart rate, blood pressure and oxygen tension were recorded continuously during the 96 h following delivery. Outcome measures included neuropathology in children who died, and motor and cognitive development at one year corrected age in children who survived. There were 22 children with a minor and 27 with a major abnormal outcome. There was a relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(85 citation statements)
references
References 14 publications
(10 reference statements)
3
82
0
Order By: Relevance
“…Matsuda et al (1999) reported that 5 of 6 fetal sheep with hemorrhagic hypotension exhibited periventricular white matter injuries similar to clinical PVL and neither of the controls had any lesions. Postnatal hypotension was associated with an increased risk of echolucency or white matter damage (MiallAllen et al 1987;Watkins et al 1989;Low et al 1993). These reports support the notion that hypotension is associated with PVL, yet some others have reported that hypotension is not associated with PVL (Trounce et al 1988;Perlman et al 1996;Dammann et al 2002;Resch et al 2004).…”
Section: Discussionsupporting
confidence: 66%
“…Matsuda et al (1999) reported that 5 of 6 fetal sheep with hemorrhagic hypotension exhibited periventricular white matter injuries similar to clinical PVL and neither of the controls had any lesions. Postnatal hypotension was associated with an increased risk of echolucency or white matter damage (MiallAllen et al 1987;Watkins et al 1989;Low et al 1993). These reports support the notion that hypotension is associated with PVL, yet some others have reported that hypotension is not associated with PVL (Trounce et al 1988;Perlman et al 1996;Dammann et al 2002;Resch et al 2004).…”
Section: Discussionsupporting
confidence: 66%
“…19 Whether in small or large prematures, MAP increased from birth to 24 hours. 8,10,14,21,24,29 Our data show that concordant large, concordant small, discordant large, discordant small, and TTTX small infants all followed similar trends. As Heigy et al 27 summarized, ''Transitional postnatal changes in cardiac output and vascular resistance are similar in all infants regardless of birth weight.…”
Section: Cordero and Johnsonmentioning
confidence: 54%
“…NEONATAL HYPOXIA IS A COMMON CONDITION that results in serious morbidity and mortality in newborns (9,19). The ability of the newborn to adapt to low O 2 depends on a multitude of physiological changes.…”
mentioning
confidence: 99%